Contextual-Based Digital Flashcard Learning Media in Improving Students’ Cognitive Learning Outcomes in Grade V Elementary School Pancasila Education Learning - Ni Kadek Manis Priska Astuti; I Made Tegeh; Ni Wayan Eka Widiastini (Indonesian Journal of Instruction, 2026)
The low cognitive learning outcomes of students in Pancasila Education indicate the need for innovative learning media that can improve conceptual understanding in a contextual and engaging manner. This study aims to analyze the design, validity, and effectiveness of contextual based digital flashcard media in improving students’ cognitive learning outcomes. This study employed a research and development design using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects involved 30 fifth grade elementary school students. Data were collected through tests, expert validation sheets, and student response questionnaires. Data analysis was conducted using quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistics through the t-test. The results showed that the digital flashcard media were systematically developed following the ADDIE stages and achieved a very high level of validity based on the evaluations of material experts, instructional design experts, media experts, and student trial results. The effectiveness test results indicated a significant improvement in students’ cognitive learning outcomes after the implementation of the media. The findings conclude that contextual based digital flashcard media are effective as an innovative learning medium to improve the quality of Pancasila Education learning. The implications of this study emphasize the importance of utilizing interactive digital media to support more engaging, meaningful, and student-centered learning.